2014
DOI: 10.1055/s-0034-1394089
|View full text |Cite
|
Sign up to set email alerts
|

Staple Line/Anastomotic Reinforcement and Other Adjuncts: Do They Make a Difference?

Abstract: ). CME Objectives: At the completion of this article the reader should be able to summarize the complications of stapled anastomoses and the various staple line reinforcement agents.The first gastrointestinal anastomosis was performed over 200 years ago.1 Since then, there has been a push to improve anastomotic techniques with the goals of reducing complications, standardizing methods, and reducing operative time. These goals led to the development of the surgical stapler and the subsequent technological impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A number of factors influence anastomosis healing, including control of the systemic disease. Regarding systemic disease, both bursting pressure and collagen content of colonic anastomoses are negatively affected in the presence of abdominal sepsis [ 12 ]. To prevent impaired healing, reinforcement methods have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors influence anastomosis healing, including control of the systemic disease. Regarding systemic disease, both bursting pressure and collagen content of colonic anastomoses are negatively affected in the presence of abdominal sepsis [ 12 ]. To prevent impaired healing, reinforcement methods have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Some other adjuncts for reinforcing the staple line for better apposition of tissue and added tensile strength have been described in the literature. Options include buttress with sutures, omentum, mesenteric flaps or synthetic materials ( 43 ). Fibrin and other associated sealants are purported to form a scaffold resistant to tension and compression while still remaining porous to cytokines and other immune cells essential for healing ( 44 - 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was a retrospective, uncontrolled study, so this single institution's experience provided low‐grade evidence. A systematic review concluded that biological materials are a promising prospect for anastomotic reinforcement in gastrointestinal anastomosis , but this needs to be further investigated in well‐designed prospective studies on LTG. The discussion on reinforcement of the duodenal stump to prevent duodenal stump fistula has been ongoing for decades in both conventional open surgery and laparoscopic gastrectomy.…”
Section: Discussionmentioning
confidence: 99%